2015
DOI: 10.4103/2008-322x.163780
|View full text |Cite
|
Sign up to set email alerts
|

Foveal structure in macula-off rhegmatogenous retinal detachment after scleral buckling or vitrectomy

Abstract: Purpose:To evaluate foveal microstructural changes and to determine its association with visual outcomes after reattachment of rhegmatogenous retinal detachments (RRDs) by scleral buckling (SB) or pars plana vitrectomy (PPV).Methods:Using spectral domain optical coherence tomography (SD-OCT), foveal microstructure in eyes with macula-off RRD were studied 1, 3, 6, 9, 12 and 15 months after PPV or SB and correlated with visual outcomes.Results:Forty-two eyes were included in the final analysis. Even with improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…These postoperative effects are seen as a result of hypoxia that occurs after macular Retinal detachment leads to deterioration in the field of vision. Despite good surgical results, visual acuity recovery may be disappointing for the patient, even in a clinically normal retina due to microstructural changes in the macula (4). The retina has a dual blood supply -from the choroid and its own vasculature, originating from the central retinal artery, a branch of arteria ophthalmica.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These postoperative effects are seen as a result of hypoxia that occurs after macular Retinal detachment leads to deterioration in the field of vision. Despite good surgical results, visual acuity recovery may be disappointing for the patient, even in a clinically normal retina due to microstructural changes in the macula (4). The retina has a dual blood supply -from the choroid and its own vasculature, originating from the central retinal artery, a branch of arteria ophthalmica.…”
Section: Discussionmentioning
confidence: 99%
“…Отлепването на ретината води до дефект в зрителното поле. Въпреки добрите хирургични резултати, зрителното възстановяване може да бъде разочароващо за пациентите, дори при клинично нормално изглеждаща ретина, дължащо се на незначителни промени в макулната микроструктура (4). Ретината има двойно кръвоснабдяване -от хороидеята и от собствената си съдова мрежа, произхождаща от артерия централис ретине, клон на артерия офталмика.…”
Section: обсъжданеunclassified
“…Studies [ 1 , 2 , 3 ] based on OCT reported different morphologies and complication of retinal reattachment correlated to a lower best-corrected visual acuity (BCVA), a cystoid macular edema (CME), persistent subretinal fluid (PSF), the formation of epiretinal macular membranes (ERM), and the disruption of the inner segment/outer segment (IS/OS). In PPV surgery, current studies relate the possible role of retinal shift on visual acuity [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the anatomical success is not always linked to functional visual recovery and involvement of the macula in the retinal detachment pathogenesis is one of the most important prognostic factors for visual prognosis [ 8 ]. In clinical practice the combination of optical coherence tomography (OCT) and optical coherence tomography angiography (OCTA) has allowed a more detailed study of some suboptimal functional recovery causes after surgery, including a refractory cystoid macular edema (CME), persistent subretinal fluid (SRF) and epiretinal membrane (ERM) combined with alteration of the inner segment/outer segment (IS/OS) [ 9 , 10 , 11 , 12 , 13 ], and a more accurate analysis of the pathophysiological changes occurring in the macular microcirculation in retinal diseases, such as diabetic retinopathy, age-related macular degeneration, retinal vein occlusions, uveitis and macular telangiectasias [ 14 ]. Several studies have investigated retinal microvasculature and its changes in ocular diseases after vitreoretinal surgery.…”
Section: Introductionmentioning
confidence: 99%